Recycled concrete aggregate and cinder gravel as base course construction materials: DOI registering (Advances in Civil and Architectural Engineering, 2024)
In this research, the potential use of recycled concrete aggregate (RCA) and CG as a base course construction material was investigated. A laboratory test involving the mechanical stabilization of RCA and CG was conducted to examine their physical properties. Eight samples of RCA blended with CG in varying proportions from 0% to 100 % with 10 % variation were studied. The laboratory test results indicate that 100 % CG yields specific gravity (SG), aggregate crushing value (ACV), aggregate impact value (AIV), Los Angeles abrasion (LAA), flakiness index (FI), elongation index (EI), plasticity index (PI), water absorption, soundness, and California bearing ratio (CBR) values of 2,54 %, 38,37 %, 20,10 %, 33,17 %, 5,59 %, 12,09 %, 0,90 %, 3,52 %, 10,60 %, and 38,08 %, respectively. The results for 100% RCA show SG, ACV, AIV, LAA, FI, EI, PI, water absorption, soundness, and CBR values of 2,70 %, 9,56 %, 5,30 %, 9,20 %, 15,30 %, 15,84 %, NP, 0,23 %, 1,49 %, and 105,87 %, respectively. These results also fail to meet the gradation requirements based on ERA standard specifications. Therefore, mechanical stabilization was adopted to improve the physical properties of the samples. Blending 60 % RCA with 40 % CG resulted in SG, ACV, AIV, LAA, FI, EI, PI, water absorption, soundness, and CBR values of 2,65 %, 19,46 %, 10,70 %, 10,88 %, 16,15 %, 22,01 %, NP, 0,26 %, 2,09 %, and 101,98 %, respectively. At this proportion, the gradation aligns with the required ERA standard specifications for GB2 and GB3 materials. Therefore, CG up to 40 % by weight with 60 % RCA is viable for road base course construction, especially when readily available or nearby.